2021
DOI: 10.1016/j.jacc.2021.04.102
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and Benefit of PCSK9 Inhibition in Patients With Nominally Controlled LDL Cholesterol

Abstract: BACKGROUND Guidelines recommend nonstatin lipid-lowering agents in patients at very high risk for major adverse cardiovascular events (MACE) if low-density lipoprotein cholesterol (LDL-C) remains ≥70 mg/dL on maximum tolerated statin treatment. It is uncertain if this approach benefits patients with LDL-C near 70 mg/dL. Lipoprotein(a) levels may influence residual risk. OBJECTIVES In a post hoc analysis of the ODYSSEY Outcomes (Evaluation of Cardiovascular Outcomes Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 29 publications
2
33
0
1
Order By: Relevance
“…As reported by the investigators of the ODYSSEY Outcomes trial, the greatest benefit of PCSK9i on MACE risk among patients with recent acute coronary syndrome were those with optimal LDL-C levels and mildly elevated Lp(a) [43]. Taking into account that similar findings were obtained in the FOURIER study [44], Lp(a) could be a reliable biomarker of residual risk, although certain confounding effects remain due to its potential role in atherothrombosis.…”
Section: Lipoprotein(a)supporting
confidence: 58%
“…As reported by the investigators of the ODYSSEY Outcomes trial, the greatest benefit of PCSK9i on MACE risk among patients with recent acute coronary syndrome were those with optimal LDL-C levels and mildly elevated Lp(a) [43]. Taking into account that similar findings were obtained in the FOURIER study [44], Lp(a) could be a reliable biomarker of residual risk, although certain confounding effects remain due to its potential role in atherothrombosis.…”
Section: Lipoprotein(a)supporting
confidence: 58%
“…Mipomersen, an antisense oligonucleotide against apolipoprotein B [68][69][70][71], had the potential benefit to reduce Lp(a) by 20%, but this drug is approved by the FDA only as an orphan drug for homozygous familial hypercholesterolemia [72]. Currently, the only drugs on the market which can decrease Lp(a) significantly (about 25%) are proprotein subtilisin/kexin type 9 (PCSK9) inhibitors-alirocumab and evolocumab [73,74]. A post hoc analysis of the Odyssey outcomes study suggested that a part of the benefits of alirocumab in reducing ASCVD events could be ascribed to its Lp(a) lowering effects, mainly on a subgroup of patients with high Lp(a) levels that had a recent myocardial infarction [75].…”
Section: Discussionmentioning
confidence: 99%
“…12 However, a most recent study in 18 924 patients with recent acute coronary syndromes and LDL-C 70 mg/dl on optimized statin therapy demonstrated that PCSK9i offered incremental clinical benefit only when Lp(a) levels were at least mildly elevated. 13 Another study revealed recently a substantial prevalence of discordance in LDL-C and Lp(a) reduction in response to PCSK9i administration, particularly when considering higher baseline Lp(a) levels. 14 Hence, based on the above, we understand that it remains difficult to separate the protective effects of PCSK9i through LDL-C and/or Lp(a) lowering.…”
Section: To the Editormentioning
confidence: 99%
“…A post hoc ODYSSEY pooled analysis, investigating the PCSK9i-induced Lp(a) reductions in association with MACCE occurrence, concluded that Lp(a) reductions were not associated with MACCE independently of LDL-C reductions 12 . However, a most recent study in 18 924 patients with recent acute coronary syndromes and LDL-C ∼70 mg/dl on optimized statin therapy demonstrated that PCSK9i offered incremental clinical benefit only when Lp(a) levels were at least mildly elevated 13 . Another study revealed recently a substantial prevalence of discordance in LDL-C and Lp(a) reduction in response to PCSK9i administration, particularly when considering higher baseline Lp(a) levels 14 …”
mentioning
confidence: 99%